STRATEGIC OF CORONAVIRUS DISEASE-19 (COVID-19) VACCINE SERVICES IN BANDUNG CITY GOVERNMENT - Fidowaty, Tatik; Wulantika, Lita; Mais, Rimi Gusliana; Susanti, Rini Ayu; Aryanti, Dian (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The aim of this research is to look at the strategy for providing Covid-19 vaccine services in Bandung City. A vaccination strategy needs to be implemented because the Covid virus is very dangerous and can kill human lives, with the potential for very fast transmission. So it is very urgent to provide vaccine services as a solution to suppress the spread of Covid-19. The method used in this research is a descriptive method and a qualitative approach. Data collection techniques use literature study, observation and in-depth interviews. The research results show that the Bandung City government's strategy in administering the Covid 19 vaccination has been working well. The strategy carried out by the Bandung City government is to make community health centers (puskesmas) the spearhead of providing the Covid-19 vaccine, collaborating with various agencies, providing vaccines based on government administration through RT/RW, vaccination in shopping centers such as malls, markets, terminals and tourist attractions. Apart from that, vaccination registration can be done online and using social media as a source of Covid-19 vaccination information.